The effects of weather, harvest frequency, and rotation number on yield of short rotation coppice willow over 10 years in northern Japan. (November 2020) - Harayama, Hisanori; Uemura, Akira; Utsugi, Hajime; Han, Qingmin; Kitao, Mitsutoshi; Maruyama, Yutaka
Abstract: Under global warming, expectations for woody biomass as a renewable energy are increasing. Short rotation coppice willow is the most widely planted energy wood crop. In this study, we examined the effect of harvest frequency on willow yield across multiple harvest rotations, something which is poorly understood. We planted 18 clones of Salix pet-susu and S. sachalinensis at a density of 25, 000 or 16, 667 cuttings ha −1 in Hokkaido, northern Japan, and harvested either annually or biennially for 10 years (2009–2018). Annual variation in willow yield per stool was analyzed using five linear mixed-effect models incorporating the number of rotations, harvest interval, and weather parameters during the growing season with clones and plant density as random factors. Number of rotations had a significant negative effect on annual yield in all five models. We estimated that yield could be halved over 10 consecutive years of harvesting. In three out of the five models, biennial harvesting had a significant positive effect on yield in comparison with annual harvesting. In addition, we found that weather conditions, such as hours of sunshine during growing season, air temperature in May (when leaf flushing occurs), and precipitation in July (when vigorous height growth occurs) have significant positive effects on willow yield. These results suggest that, to maintain willow vigor for longer time periods biennial, or more than two-year-harvest, cycle is recommended rather than annual harvest. Highlights: Willow was annually or biennially harvested for 10 consecutive years. The effect of harvest and weather conditions on yield was analyzed. Rotation number had a significant negative effect on yield. Biennial harvesting may reduce the yield decline. Weather conditions affecting willow yield were also revealed.